ADULT EDUCATION IN SURAH AL-AN'AM VERSES 74-75 - Dharmawan, Arief; Lubis, Saiful Akhyar; Nahar, Syamsu (Universitas Dharmawangsa, 2024)
This study aims to explain adult education in the Quran at surah al-An’am verses 74-75. This research is a qualitative research based on the tahlili method. The data analysis technique uses content analysis. The method of tahlili is used by the procedure of explaining the relationship of the verse which will be interpreted by the previous paragraph or after it or with the previous or subsequent surah; explain asbab nuzul; analyzing vocabulary; explain the meaning contained in each verses; and draw a conclusion. These verses illustrate the interaction between Prophet Ibrahim (Abraham) and his father, as well as his journey toward certainty through contemplation and divine demonstration. The analysis reveals that Prophet Ibrahim’s approach reflects key characteristics of adult learning, such as intrinsic motivation, a focus on real-life experiences, and a learning process that is both emotional and intellectual. Two prominent learning methods identified are the method of admonition and questioning, used to raise awareness, and the method of demonstration, used to strengthen conviction. These findings offer valuable insights into the development of Islamic learning approaches grounded in revealed knowledge, especially in adult education, emphasizing experience, internalization, and learner autonomy.